Iklim Belajar Demokratis dalam Penerapan Manajemen Berbasis Sekolah di Sekolah Dasar - Jumiyati Jumiyati (Universitas Negeri Malang, 2016)
The purpose of this survey was to describe the democratic atmosphere of classrooms of the schools applying school-based management. Questionnaires were distributed to 116 teachers and 1511 students of 16 primary schools. The results show that (1) the democratic climate was of moderate level, (2) more variation of democratic climate was found at the student level than at the school level, (3) factors influencing such a climate were students gender, parents level of education, family learning support, teachers gender, teachers level of education and teaching experience, and (4) schools applying school-based management outperformed compared to those not applying it.